Enzimas hidrolíticas produzidas por microrganismos isolados de ambiente lótico com potencial na biorremediação de efluentes de laticínio - Sherer, Marilene Tonin (2021)
Yeasts represent a very diverse group of microorganisms that produce enzymes with peculiar characteristics, such as specificity, diversity and large-scale production capacity. In addition, they have a broad biotechnological potential and, also as bioremediation, and the obtaining of this product takes place through fermentative processes. The present work aimed to produce hydrolytic enzymes from yeasts isolated from the Toledo River, Toledo-PR, and subsequent application in the treatment of dairy wastewater. The methodology initially used was cup plate, which showed promising enzymatic index. All 24 yeasts tested were positive for at least one of the enzymes studied in the plate tests. Of the isolates, 20 were positive for lipases; 11 for amyloses; 15 for proteases, and 23 for cellulases. The microorganism selected for bioremediation processes was yeast (Apiotrichum mycotoxinivorans) JC074, isolated from the Toledo River, in the City of Toledo-PR. This yeast was selected because it was the best producer of lipases in the screening test. Lipase was produced by SSF using sunflower seed bran (Helianthus annuus) as substrate, with granulometry of between 1.19 mm (16 Mesh) and 2.0 mm (10 Mesh), 55% moisture, 108 spores/g at 28⁰ C. Lipase produced by SSF was used in bioremediation experiments (shaker at 150 rpm, 37⁰ C and 168 hours) to reduce the oil & greases (O&G) levels of an effluent from a dairy of the municipality of Santa Lucia-PR. In SSF experiments, it was noted that the highest lipolitical activity (111.10 U) was obtained after 72 hours of fermentation. The results obtained were promising concluding that the effluent treatment of the dairy industry with enzimatic extract of lyase obtained from the isolation of yeasts from continental Waters is feasible, and can be used in the treatment of effluent contributing to the reduction of the environmental impacto f dairy products.